Waste Bank Education Program And Its Impact On Environmental Awareness And Community Participation - Yoenanda Maulana; Arzeti Adhelin; Gias Rahman Alfarisyi; Gilang Septiana (Pengabdian: Jurnal Abdimas, 2024)
Background. Community Service is an activity that aims to help the community in several activities without expecting any form of reward. In general, this program is designed by various universities in Indonesia to make a real contribution to the nation, especially in developing the welfare and progress of the Indonesian nation. Community service activities are one part of the Tri Dharma of Higher Education. Purpose. The Waste Bank education program aims to increase environmental awareness and community participation in waste management. This research explores the impact of the program on increasing environmental awareness and levels of community participation in the communities involved. Method. Based on the theory of pro-environmental behavior and social participation, this research uses survey and interview methods to collect data from 150 respondents who participated in the Waste Bank program in several locations in Indonesia Results. The research results show that the Waste Bank education program significantly increases participants' environmental awareness and encourages active participation in waste management. Conclusion. In conclusion, this program contributes to changes in community behavior towards more sustainable and environmentally friendly waste management.